การผลิตพลังงานไฟฟ้าด้วยเทอร์โมอิเล็กตริกจากเครื่องปรับอากาศ - ทองกุลภัทร์ สรายุธ; ศรีธนาอุทัยกร พัชรนันท์ (RMUTSB ACADEMIC JOURNAL, 2017)
บทคัดย่อไม่สมบูรณ์ Electrical energy generation by thermoelectric from an air conditioner This paper proposed a thermoelectric to generate an electrical energy from the different temperature between hot and cool sides of an air conditioner. A split type air conditioner, the temperature of drained water was 20 - 25oC and the temperature of the hot side of the air conditioner, the compressor, was 50 - 70oC. The temperature differed from these two sources which was enough to produce the electrical energy. Thus, a study of energy conversion from different temperature to electric energy by the thermoelectric was considered. The experimental system was 10 sets of thermoelectric that were compounded connection. They produced 44.16 watts-hour of electric power.